THE ROLE OF THE COMMUNITY IN DEMANDS FOR COMPENSATION LOSSES ACCORDING TO LAW ON PROTECTION AND MANAGEMENT ENVIRONMENT - Effendi, Prihatin; White, Mathew A. (SYNTIFIC, 2025)
Background. Community involvement is very important in managing the environment to create a healthy living space. Health is not just about physical condition or a clean environment, but also about overall well-being. Everyone has the same rights and responsibilities in protecting the environment. Communities often work with NGOs to deal with pollution and environmental damage. Research Methods. This Research uses a legal study approach by looking at laws and regulations related to community roles in environmental protection. It also explores how people and NGOs solve environmental problems through mediation instead of going to court. Findings. The study found that while people and NGOs prefer using mediation to solve environmental disputes, there are problems with legal certainty. This makes the mediation results unclear or hard to enforce. Conclusion. To fix this, a mediation process that is officially recognized by the court is needed. This will help provide clear legal outcomes and fairness for everyone involved.